Розвиток сценарної справи на Одеській кіностудії в першій половині 1920-х рр. (на основі біографій перших сценаристів) - Лізавенко, Г. (Чорноморська минувшина, 2016)
Мета даної роботи полягає в дослідженні становлення сценарної справи на Одеській кіностудії. Розвиток цієї ніші німого кінематографу був дуже важливим і на даному етапі ми спостерігаємо за першими кроками сценаристів у новій для них справі. Проаналізовано умови, в яких здійснювалось затвердження та розвиток сценарної справи. До першої половини 1920-х рр. ще не було чіткої грані між режисерами, сценаристами та акторами. Усі ці всі посади могла займати одна людина, але саме з цього часу ми можемо спостерігати за виокремленням окремої когорти митців – сценаристів. У подальшому сценарна і режисерська справа перепліталась у їхніх біографіях, але в даній роботі ми зробили аспект саме на внеску відомих особистостей у сценарну справу. Розглянуто особливості та фактори переходу Одеської кіностудії до системи ВУФКУ, що сприяло появі нових режисерів, операторів, художників, сценаристів. Зазначено, що на Одеській кіностудії працювали талановиті сценаристи, які закладали маленькими камінчиками фундамент майбутньої кінематографії. Саме починаючи з одеських корифеїв кінематографу в Україні створювалось своє кіно. Незважаючи на культурні репресії з боку влади, яка спочатку давала можливості для розвитку, а потім знищувала митців і їх творіння, саме завдяки сценаристам які працювали в Одесі ми можемо насолоджуватися як фільмами того часу так і чудовою та правильною постановкою фільмів сьогодні. The purpose of this work is to study the formation screenplay case for Odessa Film Studio. The development of this niche silent cinema was very important and at this stage we are witnessing the first steps for the writers, the new case for them. The conditions, which carried out the approval and development of the screenwriting business. The first half of 1920 there was no clear line between directors, writers, actors, all these roles could take one person, but from that time we can see the form the separate cohort of artists – writers. Pioneers of Ukrainian film industry had overcome difficulties. Regular production of films was not established from the start. There has never been factories for the production crew, projection and lighting equipment, film crew bought abroad. Insufficient technical equipment of studios initially limited the possibilities of enthusiasts who tried to organize a clear, rhythmic, planned and cost-effective production. In Odessa film studio career working talented writers who laid the foundation stones for future small cinema. It is learned, made the first attempt, perhaps they do not always work, not always their vision of cinema scenario to meet the requirements of the then government. The government, which gave them the opportunity to develop first, work on it, and then she herself destroyed. The so-called sacrifice in Ukraine is too ambitious to forget it, and now, due to the discovery of new facts repression, opening archives are seen in a new, space and no less tragic. Without a doubt, the rulers limitation of any seeds of nationalism. That since our cinema luminaries Odessa, Ukraine needs a home and its movies, thanks to screenwriters who worked in Odessa we can enjoy a movie at the time and wonderful and correct statement of movies today. In the following case scenario and director interwoven in their biographies, but in this work we were doing aspect is to contribute celebrities in screenwriting business. Цель данной работы заключается в исследовании становления сценарного дела на Одесской киностудии. Развитие этой ниши немого кинематографа было очень важным, на данном этапе мы наблюдаем за первыми шагами сценаристов в освоении нового дела. Проанализированы условия, в которых осуществлялось утверждение и развитие сценарного дела. До первой половины 1920-х годов еще не было четкой грани между режиссерами, сценаристами и актерами. Все эти должности мог занимать один человек, но именно с этого времени мы можем наблюдать за выделением отдельной когорты деятелей – сценаристов. Пионеры украинского кинопроизводства преодолевали немало трудностей. Регулярный выпуск фильмов не был налажен с начала. Еще не было заводов по производству съемочной, проекционной и осветительной аппаратуры, съемочную пленку покупали за рубежом. Недостаточное техническое оснащение студий на первых порах ограничивало возможности тех энтузиастов, которые пытались организовать четкое, ритмичное, плановое и рентабельное производство. В Одесской киностудии работали талантливые сценаристы, которые закладывали маленькими камешками фундамент будущей кинематографии. Именно начиная с одесских корифеев кинематографа, Украина имеет свое кино, именно благодаря сценаристам которые работали в Одессе мы можем наслаждаться как фильмами того времени так и замечательной и правильной постановкой фильмов сегодня. В дальнейшем сценарное и режиссерское дело переплеталось в их биографиях сценаристов, но в данной работе мы сделали аспект именно на ту лепту, которую известные личности внесли в сценарное дело.